Celebrity Crises on Twitter - Bruns, Axel; Highfield, Tim; Vimieiro, Ana; Vimieiro, Renato; Sauter, Theresa; Puschmann, Cornelius (AoIR Selected Papers of Internet Research, 2013)
Recently, Twitter has strongly promoted its service as a means of following the day-to-day activities of celebrities in media, sports, and politics, and perhaps of tweeting about and even receiving the occasional reply from such accounts. Indeed, celebrity accounts are amongst the most-followed accounts on Twitter (Marwick and boyd, 2011). Users employ them to attain constant live updates on the latest gossip around their favourite celebrities (Cha, et al., 2010) and to feel closer to them. This points in part to the use of Twitter for lurking or “listening” (Crawford, 2009) rather than necessarily for highly active participation.Twitter has also been recognised as a medium for “ambient news” (Hermida, 2010; Burns, 2010): while its everyday uses may be diverse and centred around mundane activities, when major news breaks, Twitter users become actively engaged in sharing the latest rumours and updates and thereby “working the story” (Bruns & Highfield, 2012) as part of a collaborative news curation process. This has been evident around key world events from natural disasters to political crises over recent years: coordinated especially through hashtags, ad hoc publics (Bruns & Burgess, 2011) form on Twitter to discuss and evaluate such breaking news events.This panel brings together a collection of papers which use innovative social media analytics techniques and approaches to examine a series of events which are situated at the intersection of celebrity- and breaking news-related uses of Twitter: they examine the Twitter userbase's reaction to a number of high-profile celebrity crises. Papers in this panel explore the hypothesis that in response to such crisis events - such as Lance Armstrong's doping confession, the Pope's resignation, or Oscar Pistorius's arrest on murder charges, but also to the everyday crises of a national government -, the Twitter audiences of these accounts shift to a more active mode of participation which seeks to make sense of the unfolding story.Through detailed observations of the Twitter reaction to these celebrity crisis events, we are able to track a number of simultaneous processes which shed light on more general patterns of Twitter usage: from a formal perspective, the emergence of shared hashtags, memes, and other user-created ad hoc conventions for coordinating the discussion of the crisis event; from a network perspective, the emergence and interconnection of key participants in the unfolding discussion; and from a content perspective, the formation of public opinion(s) as a greater amount of information becomes available and is shared, discussed, and evaluated.These case studies reveal how everyday individuals use Twitter to engage with their favourite celebrities in new ways that bring them closer together and enable them to react immediately to breaking news, as well as actively direct questions at and demand statements from these public figures. In this way, we can detect an intermingling of traditional news reporting and public reaction to events that heightens the mutual construction of stories within networks of humans and technologies that include multiple actants - such as the celebrities (and their PR teams) at the head of the crisis, journalists, official governmental bodies, and citizens, all trying to make sense of the events and constructing stories. Importantly, this ad hoc engagement contributes to shaping the unfolding of crisis events and their aftermath.An observation of such developments through the lens of quantitative and qualitative evaluation of large datasets that pertain to these cases provides novel and unprecedented perspectives on public communication which - if not simply representative for overall world opinion - nonetheless indicate that online public engagement is becoming an increasingly important and influential component of the global public debate.References:Bruns, A., & Burgess, J. (2011). The use of twitter hashtags in the formation of ad hoc publics. European Consortium for Political Research conference, Reykjavík, 25-27 Aug. 2011. Reykjavík. Retrieved from http://eprints.qut.edu.au/46515/Bruns, A., & Highfield, T. (2012). Blogs, Twitter, and Breaking News: The Produsage of Citizen Journalism. In R. A. Lind (Ed.), Produsing Theory in a Digital World: The Intersection of Audiences and Production (Vol. 30, pp. 15–32). New York: Peter Lang.Burns, Alex (2010, May) “Oblique Strategies for Ambient Journalism.” M/C Journal 13(2). http://journal.media- culture.org.au/index.php/mcjournal/article/view/230, accessed 1 Aug. 2011.Cha, M., Haddadi, H., Benevenuto, F., & Gummadi, K. P. (2010, May). Measuring user influence in twitter: The million follower fallacy. In 4th international aaai conference on weblogs and social media (icwsm) (Vol. 14, No. 1, p. 8).Crawford, Kate (2009) “Following You: Disciplines of Listening in Social Media.” Continuum: Journal of Media & Cultural Studies 23(40): pp. 525-35.Hermida, Alfred (2010, May). “From TV to Twitter: How Ambient News Became Ambient Journalism.” M/C Journal 13(2). http://journal.media-culture.org.au/index.php/mcjournal/article/view/220, accessed 1 Aug. 2011.Marwick, A. E. and boyd d (2011). I tweet honestly, I tweet passionately: Twitter users, context collapse, and the imagined audience. New Media & Society, 13(1), 114-133.